KOMPARASI PENGELOLAAN MINYAK DAN GAS BUMI MENURUT SISTEM EKONOMI KAPITALISME DAN ISLAM (STUDI KASUS DI INDONESIA) - Yusanto, Ismail (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2024)
Indonesia possesses abundant natural resources, particularly oil and natural gas, these resources have not yet been. The main problem is high fuel prices. Indonesia is one of the world's largest oil producers and has significant potential, oil production declines annually, while aging wells and a lack of new fields are reducing production levels. Why is this happening? Therefore, this study aims to compare oil and gas management from a capitalist and Islamic perspective in Indonesia. This study uses qualitative research methods with library research. The results show that before 2001, Law Number 8 of 1971 regulated the oil and gas industry in Indonesia with a government monopoly. Economic liberalization and global influences have driven changes in oil and gas regulations,including the elimination of subsidies, the privatization of state-owned enterprises, and international involvement, from an Islamic economic perspective, are publicly owned. comparison of the management systems, nature of ownership and control, management, regulation, distribution, and implications between the two systems reveals significant differences. the government must openly declare that the system being implemented is capitalism, so that the public can gain a broader perspective, especially regarding the distribution of wealth and opportunity, as many question the fairness of the current system.